Cooperative learning in English language classrooms: teachers’ perception and actions : - Lê, Thị Trúc Đào (Trường đại học Cần Thơ, 2018)
This study was conducted to investigate teachers’ perceptions toward cooperative learning in teaching and learning English. In particular, the study aims to investigate if the participating teachers have positive perceptions toward this method and its impact on their English language classrooms as well as aims to find out their practices in their English language classrooms in order to promote cooperative learning.